Perancangan Prototype GPS Tracker via SMS Berbasis Mikrokontroler Arduino Nano - Abrar; Munandar; Iqbal, Taufiq (Jurnal Sistem Komputer (SISKOM), 2023)
The Global Positioning System (GPS) navigation system has become an inseparable necessity in the modern era, allowing users to know their position with high accuracy and provide precise time information anywhere. This research aims to design a GPS Tracker prototype based on the Arduino Nano microcontroller which is capable of tracking position using short messages (SMS). This prototype uses an Arduino Nano microcontroller, Ublox Neo 6M GPS module, and SIM 800L GPRS network module to process and transmit coordinate data via GPRS waves. This research uses research and development (R&D) methods with the steps of data collection, analysis, design, development and evaluation of solutions. Primary and secondary data were obtained through technical observation, interviews and data analysis. Data analysis methods include descriptive analysis and anomaly analysis. The research results show that this prototype can send coordinate data via SMS with quite high accuracy. This prototype is expected to provide benefits in location-based surveillance and monitoring without requiring an active internet connection.